2018
DOI: 10.1016/j.str.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Mechanism of Procollagen C-Proteinase Enhancer

Abstract: et al. (2017). RNAibased treatment of chronically infected patients and chimpanzees reveals that integrated hepatitis B virus DNA is a source of HBsAg. Sci. Transl. Med. 9, 9. . (2017).Chimeric rabbit/human Fab antibodies against the hepatitis Be-antigen and their potential applications in assays, characterization, and therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Therefore, PCPE1 has pleiotropic effects in promoting collagen deposition. PCPE1 works via binding specifically to the type I procollagen C-propeptides via the calcium binding motif in CUB domain, so as to render the substrate a more suitable conformation to be cleaved by BMP1 [16] . More specifically, the ability of Pcolce1 to prompt collagen deposition can be only through its effect on BMP1 [26] , and PCPE1 only stimulates the activity of BMP1 when the substrates are fibrillar procollagen types I and III [27] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, PCPE1 has pleiotropic effects in promoting collagen deposition. PCPE1 works via binding specifically to the type I procollagen C-propeptides via the calcium binding motif in CUB domain, so as to render the substrate a more suitable conformation to be cleaved by BMP1 [16] . More specifically, the ability of Pcolce1 to prompt collagen deposition can be only through its effect on BMP1 [26] , and PCPE1 only stimulates the activity of BMP1 when the substrates are fibrillar procollagen types I and III [27] .…”
Section: Discussionmentioning
confidence: 99%
“…CD31 immunofluorescent results showed a significant lower density of retinal vascular of Pcolce1 -/mice than that of WT mice (Figure 2), indicating that Pcolce1 KO leads to less retinal angiogenesis, which was consistent with our previous results. Pro-collagen in Pcolce1 -/-Mice From both Medium and Embryo Fibroblasts As previously demonstrated that Pcolce1 could enhance the procollagen C-proteinase (PCP) activity of bone morphogenetic protein 1 (BMP1), which can cleave C-propeptides from the procollagen precursors to form mature collagen [16] . To further investigate whether PCPE1 can enhance the cleavage activity of BMP1 and result in more mature collagen produce, in vitro procollagen α1(I) cleavage assays were performed in MEF cells.…”
Section: Quantitative Real-time Polymerase Chain Reaction Analysismentioning
confidence: 92%
“…10 PCPE1 has been reported to bind to C-terminal propeptides of procollagens (eg, PICP) through its 2 CUB domains resulting in a conformational change that enhances BMP1 activity. [11][12][13] Furthermore, PCPE1 also contains a netrin-like domain which has been demonstrated to inhibit MMPs (matrix metalloproteinases) activity by direct interaction or indirect regulation through heparan sulfate binding. 14,15 Moreover, the expression and synthesis of PCPE1 have been described to be upregulated by TGFb, aldosterone, and ascorbic acid in cardiac rat fibroblasts.…”
Section: Introductionmentioning
confidence: 99%